Risk classification of children and adolescents: priority of care in the emergency unit - Fernanda Jorge Magalhães; Francisca Elisângela Teixeira Lima; Lorena Pinheiro Barbosa; Fernanda Jorge Guimarães; Gilvan Ferreira Felipe; Karla Maria Carneiro Rolim; Essyo Pedro Moreira de Lima
ABSTRACT Objective: to evaluate the clinical conditions and the risk classification of children and adolescents treated in a hospital emergency, according to the Pediatric Risk Classification Protocol. Method: cross-sectional study, with 200 participants, using an instrument based on the Pediatric Risk Classification Protocol and using odds ratio for the analysis. Results: most participants were male patients in early childhood and who were or weren't in daycare. As for clinical conditions, most showed changes in vital (24.5%) and respiratory (20.0%) signs, most patients (57.5%) did not present pain; 35.5% were classified as urgent and 45.0% as non-urgent. There was a greater chance of being classified as very urgent (orange) when compared to non-urgent (blue). Conclusion: the protocol used contributed to an effective classification and was considered a valid and reliable health technology for determining the priority of care.